1973
DOI: 10.2307/1942161
|View full text |Cite
|
Sign up to set email alerts
|

Organization of a Plant‐Arthropod Association in Simple and Diverse Habitats: The Fauna of Collards (Brassica Oleracea)

Abstract: Collards were grown at Ithaca, New York, in two experimental habitats: pure stands and single rows that were bounded on each side by diverse, meadow vegetation. The arthropods associated with these plants were sampled on 20 dates over a 3—year period. The status of the herbivore species was measured by their rank in biomass in each sample. The two most prominent species, Phyllotreta cruciferae and Pieris rapae, maintained high status throughout the investigation, but another important species, Brevicoryne bras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

153
2,106
45
70

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,634 publications
(2,374 citation statements)
references
References 55 publications
(81 reference statements)
153
2,106
45
70
Order By: Relevance
“…Chaplin-Kramer et al (2011) and Veres et al (2013) proposed explanations for the variable effects of landscape complexity on insect pests across studies. Despite the resource concentration hypothesis (Root, 1973), large fields may favour pest dilution, resulting in a reduced abundance in regard to the field size. Moreover, although non-crop habitats can enhance natural enemies and in turn pest control, landscape complexity may also complicate their search for prey or hosts.…”
Section: At the Landscape Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Chaplin-Kramer et al (2011) and Veres et al (2013) proposed explanations for the variable effects of landscape complexity on insect pests across studies. Despite the resource concentration hypothesis (Root, 1973), large fields may favour pest dilution, resulting in a reduced abundance in regard to the field size. Moreover, although non-crop habitats can enhance natural enemies and in turn pest control, landscape complexity may also complicate their search for prey or hosts.…”
Section: At the Landscape Scalementioning
confidence: 99%
“…Because development of specialised herbivores is facilitated in homogeneous fields (i.e. resource concentration hypothesis of Root, 1973), diversifying cropping areas by mixing crops (i.e. intercropping), crop with non-crop plants (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…'Resource Concentration Hypothesis' poses that herbivores frequently forage in a density-dependent manner, and therefore increasing plant species or genotype number while keeping plant density constant reduces the probability of finding a preferred host plant species (or genotype), ultimately leading to lower herbivore abundance and damage on individual plants [21].…”
Section: The Predictive Role Of Producer and Consumer Traits Plant Trmentioning
confidence: 99%
“…A rich body of theory has been developed to predict the effects of plant diversity on communities at higher trophic levels ( [16][17][18][19][20][21][22], see Box 1). Despite this vast collection of theory behind plant diversity effects on associated faunas and the large number of empirical studies conducted thus far, formal evaluations of the mechanisms behind the observed patterns have been developed in natural communities (but see [20] for e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation